A comparison of downloads, readership and citations data for the Journal of Medical Hypotheses and Ideas. Issue 1 (March 2015) - Bazrafshan, Azam; Haghdoost, Ali Akbar; Zare, Morteza
Abstract : Graphical abstract: Abstract : Highlights: Articles published in the journal have a high rate of downloads around the world. Articles are from a variety of countries and the acceptance odds is even across regions. The journal's citation overview reflects rather a low level of impact in Scopus. Future directions are provided to promote the visibility and impact of the journal's articles. Abstract: This article reflects the comparison of downloads, readership and citation data for the Journal of Medical Hypotheses and Ideas. A brief analysis of the journal's recent performance indicates that the journal articles appear to have a high rate of downloads around the world. Its published articles are from a variety of countries and the odds of accepted articles for publication is surprisingly even across regions. However, the rate of received citations to the published articles indicated a lack of considerable impact in scholarly publications. This approach has double value as it shows the overall impact of the journal in social web as well as scholarly publications and also provides future directions for the journal's editorial boards. Altmetrics was also proposed as an alternative to the widely used citation and usage indicators in tracking the impact of individual articles.